Plant secondary metabolites: new opportunity for controlling phytoviruses - Guo, Shengxin; Guo, Xiaoqiu; Wang, Ya; Xu, Ying; Wu, Jian (Pest management science, 2025)
Phytoviruses pose a significant threat to global agriculture, causing substantial yield losses and economic damage. Traditional control measures, such as chemotherapeutics, are often ineffective and environmentally harmful, necessitating the development of sustainable alternatives. Plant secondary metabolites, including alkaloids, phenols, flavonoids, and triterpenes, have emerged as promising candidates for phytovirus management due to their diverse structures and potent antiviral activities. Herein, we present a comprehensive summary of 202 plant secondary metabolites, highlighting their mechanisms of action, such as inhibition of viral replication, interference with viral movement, and induction of plant immune responses. Notable metabolites, including antofine, quercetin, and ursolic acid, have demonstrated significant antiviral efficacy, often surpassing that of conventional agents like Ningnanmycin. However, challenges such as low stability, poor solubility, and difficulties in large‐scale production limit their practical application. To address these challenges, the field of phytovirus management must embrace interdisciplinary approaches to overcome existing challenges and unlock the full potential of plant secondary metabolites. This review tries to not only consolidate current knowledge on plant secondary metabolites but also provide a roadmap for future research and innovation to transform these natural compounds into practical tools and eco‐friendly solutions, ensuring food security in the face of evolving viral threats. © 2025 Society of Chemical Industry.